A Comparative Study on the Quality Changes of Croaker (Johnius dussumieri) Fish Stored in Slurry Ice and Flake Ice. Issue 4 (21st April 2018) - Annamalai, Jeyakumari; Lakshmi, Narasimha Murthy; Sivam, Visnuvinayagam; Chandragiri Nagaraja Rao, Ravishankar
ABSTRACT: In the present study, the effect of storage in slurry ice compared to conventional flake ice (control) on the quality of croaker ( Johnius dussumieri ) fish was evaluated. Biochemical, microbiological, and sensory analyses were performed. Total volatile base nitrogen, trimethylamine nitrogen, and pH values were lower for fish stored in slurry ice than in control. Similarly, aerobic plate count and Pseudomonas sp. count were also found at lower population levels in fish stored in slurry ice. Texture profile analysis revealed that fish stored in slurry ice showed improved texture. Based on the microbiological and sensory analysis, the shelf life of croaker fish stored in slurry ice was 15 days.